Cyclical behavior of timber mortise-tenon joints strengthened with shape memory alloy: experiments and moment-rotation model. Issue 8 (17th November 2019) - Xie, Qifang; Zhang, Lipeng; Zhou, Weijian; Wang, Long; Zhou, Tiegang
ABSTRACT: This article presents the results of a study on the cyclical behavior of mortise-tenon joints strengthened with shape memory alloy (SMA) wires. Four 1/3.52 scaled joint specimens reinforced with different number of SMA wires were subjected to low-cyclic reversed loading tests and the moment-rotation hysteretic curves were obtained. The cyclic behavior of joints strengthened with SMA were compared with that of joints strengthened with conventional reinforcement methods, such as cramp, carbon fiber, steel pins, U-shaped hoop, angle steel, curved plate, etc. Results indicated that the strength, stiffness, and energy dissipation capacity of the mortise-tenon joints strengthened with SMA were improved markedly. The residual deformation of the mortise-tenon joints strengthened with SMA is approx. 20% less than that strengthened with the conventional strengthening methods. A nonlinear model composed of one three-parameter power function and one straight line was presented for the moment-rotation of the mortise-tenon joints and good agreement between predictions and tests were observed.